The Digital Lives of Student Mothers: A Consideration of Technologies That Support or Erode the Student/Parent Boundary. Issue 154 (October 2021) - Thomas, Lisa; Talbot, Catherine V; Briggs, Pam
Highlights: Minimal work has addressed stressors experienced by student mothers, who have to juggle the demands of study and childcare. Literature on work/life balance suggests a key issue for student mothers is the management of the work-family border. We use work-family border theory to examine the role that technology plays in supporting or eroding the student and parent roles. We recommend ways boundary maintenance should be more considered in digital systems design. Abstract: A growing body of work explores the well-being of students. However, little work has addressed the experiences of student mothers, who must juggle the demands of study and childcare simultaneously. The rise of the student mother is taking place at a time when student learning and engagement as well as childcare has become highly digitised. Existing literature on work/life balance suggests a key issue for student mothers is management of the work-family border, such that they can choose to segregate or blend roles as appropriate. In this study, we used work-family border theory to examine the role that technology plays in supporting both the segregation and blending of student and parent roles, making recommendations for the ways that boundary maintenance might be more explicitly considered in digital systems design.